Advance Care Planning and End-of-Life Management of Adult Patients With Congenital Heart Disease. (January 2013) - Kovacs, Adrienne H.; Landzberg, Michael J.; Goodlin, Sarah J.
As a result of advances in the diagnosis and treatment of congenital heart disease (CHD), it is now adult care providers, rather than pediatric providers, who are faced with the majority of patient deaths. Effective advance care planning and end-of-life (EOL) care require open communication and collaboration in order to benefit patients, family members, and clinicians. Published guidelines recommend early completion of advance directives and addressing EOL issues in routine care. This article reviews the pattern of shifting CHD mortality, current knowledge regarding advanced care planning and EOL discussions with adults with CHD (ACHD), and guidelines to facilitate and optimize these important discussions.